Kelimpahan Ikan Herbivora pada Fish Apartment di Perairan Pantai Pulau Tangah Kota Pariaman, Sumatera Barat - Frimanozi, Suci; Zakaria, Indra Junaidi; Nurdin, Jabang (Metamorfosa: Journal of Biological Sciences, 2019)
Herbivorous fish have an influence on habitat quality and a major factor in determining coral reef community. This herbivorous fish used as indicator of  monitoring refers to reef resilience since of its ability to retain and restore the coral reef condition after disturbance. The presence of herbivores is important in influencing succession of algae, it can reduce and control algae on coral reefs. It’s causes in the availability of space or substrate for corals to recruit. So the research conducted that aims to know the abundance of herbivorous fish in fish apartment as one indicator of monitoring based on endurance. This study had conducted after six months of fish apartment placed in the coastal waters of Tangah Island, Pariaman City, West Sumatra. Then, the observation had done every month for six months in July 2015 - January 2016 at the location of the fish apartment. Observation abundance of herbivorous fish had done by visual census method at fish apartment location. From the results of observations for six months found 10 species of herbivorous fish with total as many as 289 individuals.  Zebrasoma scopas  is a species with the most individuals than 97 individu. However, to see the effect of herbivorous fish on coral recruitment in fish apartment needs to do further research. Keywords: abundance, herbivorous fish, fish apartment